LEXICAL FEATURES OF SENIOR HIGH SCHOOL STUDENTS’ WRITING ON RECOUNT TEXT - K. Karman (Journal of English Education, 2016)
This study was aimed to find out the lexical features of senior high school students’ writing on recount text. The corpus being analyzed in this study consists of 38 recount texts. The corpus was analyzed by using text analyzer online application. It was found that students’ vocabulary has exceeded over 853 words family. The lexical density of the students’ writing was 35.8%, and its beta alternative (readability factor) was 70.7. In accordance with the high frequency words appearing in the recount text, they were categorized into five prominent lexical classes. They are noun-pronoun to identify objects being involved in events, action verbs which refer to events, conjunction and time connectives to sequence the events, adverbs and adverbial phrases to indicate place and time, and adjectives to describe nouns. These five prominent word classes of recount text existed in the students’ writing.